The first UK survey and population estimate of breeding Snow Bunting Plectrophenax nivalis. Issue 1 (2nd January 2018) - Hayhow, Daniel B.; Eaton, Mark A.; Stanbury, Andy J.; Douse, Andy; Marquiss, Mick
ABSTRACT: Capsule: The first national survey for Snow Bunting Plectrophenax nivalis in the UK was carried out in 2011 and estimated the breeding population at 60 territories (95% confidence intervals = 48–83). Aims: To estimate breeding population size for Snow Buntings in the UK by surveying all sites with a history of breeding season occupation. Methods: Surveys were carried out in June 2011 to detect males on territory at sites where Snow Bunting had been recorded during the breeding season since 1970. Each site was visited at least once during the survey period; suitable habitat was searched and vantage point watches were conducted in order to detect singing males. Repeated visits to a sample of sites allowed a correction factor to be calculated in order to account for birds undetected during surveys. Results: In 2011, the number of Snow Bunting breeding in the UK (including adjusting for imperfect detection) is a minimum of 60 territories (95% CI = 48–83) using confirmed and probable breeding records of males. A less conservative estimate of 99 territories (95% CI = 88–114) results from including all records of males in suitable habitat. The vast majority of the population was found in the Cairngorm region, with isolated records in the north and west Highlands. Conclusion: The results of the 2011 survey are consistent with well-informed estimates of the Snow Bunting population made previously. This work provides a baseline and repeatable fieldwork and analytical methods enabling future change in the population to be quantified more rigorously.